Faktor-Faktor Yang Mempengaruhi Hasil Tangkapan Armada Perikanan Skala Kecil di Kei Kecil Bagian Timur , Kepulauan kei - Simon Marsholl Picaulima; Eko Sri Wiyono; Mulyono Sumitro Baskoro; Mochammad Riyanto (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Dynamics of small-scale fleet fisheries is the fishing effort made by small fishermen to maximize the catch in each season. Continuous fishing effort without control can have an impact on fishing fleet competition which can lead to a decrease in certain fish resources, therefore it is necessary to identify the factors that affect the catch of small-scale fishing fleets. This study aims to identify the factors that affect the catch of small-scale fishing fleets. The research method used a survey method, the determination of respondents by purposive sampling technique. The data analysis used is comparative descriptive analysis and General Linear Model. The results showed that the catches of the fishing fleets of bagan, purse seine, drift gillnet, bottom gillnet, tug line and hand line in this study were generally significantly influenced by the variable capacity of the fleet. The number and capacity of small-scale fishing fleets that are not properly controlled and regulated by the management, namely the Maluku Provincial Fisheries Service, have had an impact on the free competition of fishing fleets in every season in the Kei Islands. Competition for small-scale fishing fleets can cause fish resources to decrease from time to time, therefore it is necessary to monitor and regulate small-scale fishing fleets using input and control techniques.